ChemInform Abstract: A Gallogermanate Zeolite with Eleven‐Membered‐Ring Channels. Issue 33 (25th July 2013) - Xu, Yan; Li, Yi; Han, Yide; Song, Xiaowei; Yu, Jihong
Abstract Large pink cubic single crystals of the zeolite [Ni(dap)3]36Ni4.7 [Ga81.4Ge206.6O576] (dap: 1, 2‐diaminopropane) are hydrothermally synthesized from a mixture of GeO2, Ga(NO3)3, Ni(OAc)2, dap, and H2O in a molar ratio of 1.00:0.39:0.24:19.17:36.76 (autoclave, 180 °C, 8 d).